Combination Therapies for Biofilm Inhibition and Eradication: A Comparative Review of Laboratory and Preclinical Studies - Hawas, Sophia; Verderosa, Anthony D.; Totsika, Makrina (Frontiers in Cellular and Infection Microbiology, 2022)
Microbial biofilms are becoming increasingly difficult to treat in the medical setting due to their intrinsic resistance to antibiotics. To combat this, several biofilm dispersal agents are currently being developed as treatments for biofilm infections. Combining biofilm dispersal agents with antibiotics is emerging as a promising strategy to simultaneously disperse and eradicate biofilms or, in some cases, even inhibit biofilm formation. Here we review studies that have investigated the anti-biofilm activity of some well-studied biofilm dispersal agents (e.g., quorum sensing inhibitors, nitric oxide/nitroxides, antimicrobial peptides/amino acids) in combination with antibiotics from various classes. This review aims to directly compare the efficacy of different combination strategies against microbial biofilms and highlight synergistic treatments that warrant further investigation. By comparing across studies that use different measures of efficacy, we can conclude that treating biofilms in vitro and, in some limited cases in vivo, with a combination of an anti-biofilm agent and an antibiotic, appears overall more effective than treating with either compound alone. The review identifies the most promising combination therapies currently under development as biofilm inhibition and eradication therapies.